2004
DOI: 10.1007/s00799-003-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

From physical to digital: a case study of computer scientists’ behaviour in physical libraries

Abstract: There has been substantial research on various aspects of people's usage of physical libraries but relatively little on their interaction with individual library artefacts; that is: books, journals, and papers. We have studied people's behaviour when working in physical libraries, focusing particularly on how they interact with these artefacts, how they evaluate them, and how they interact with librarians. This study provides a better understanding of how people interact with paper information, from which we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 29 publications
(34 reference statements)
3
82
0
Order By: Relevance
“…The EBL system provides readers with instant access to a navigation panel to the left of the book that, for most books, displays some kind of ToC. The ToC is seen to be useful in decision-making in print books [2,8,10,23,25], print articles [17] and ebooks [2,10,15]. Readers in our study used the interactive ToC in the left-hand panel relatively frequently (62% of all readers), suggesting that many at the very least saw this panel.…”
Section: Document Selectionmentioning
confidence: 76%
See 1 more Smart Citation
“…The EBL system provides readers with instant access to a navigation panel to the left of the book that, for most books, displays some kind of ToC. The ToC is seen to be useful in decision-making in print books [2,8,10,23,25], print articles [17] and ebooks [2,10,15]. Readers in our study used the interactive ToC in the left-hand panel relatively frequently (62% of all readers), suggesting that many at the very least saw this panel.…”
Section: Document Selectionmentioning
confidence: 76%
“…Stelmaszweska et al's work [23] following computer scientists is the earliest published work based on observation of adults selecting books in a library. This study demonstrated that while these readers did use book content to guide their decision to some extent, they also looked at the book covers to determine books' ages and assessed the amount of dust on books to determine whether they had been recently used.…”
Section: Book Selectionmentioning
confidence: 99%
“…Key models of information seeking include elements that focus on browsing and exploration [3,4]. The literature on book seeking also shows that readers consider browsing an important part of book seeking [1,5,6]. Readers in both academic [5,7] and public [8] libraries note lack of browsing support as a reason for avoiding the use of ebooks.…”
Section: Introductionmentioning
confidence: 99%
“…Our prior work [9] leveraged two established digital library techniques-examining physical libraries [1,6,7] and transaction log analysis [10,11]-to determine whether physical layout of library shelves affects book borrowing patterns. In that work we specifically examined whether proximity to a loaned book increases the chance a book will itself be loaned: we found a strongly significant increase in this likelihood that we termed the neighbour effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation